2018
DOI: 10.20944/preprints201810.0529.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone marrow derived extracellular vesicles activate osteoclast differentiation in traumatic brain injury induced bone loss

Abstract: Traumatic brain injury (TBI) is a major source of worldwide morbidity and mortality. Patients suffering from TBI exhibit a higher susceptibility to bone loss and an increased rate of bone fractures; however, the underlying mechanisms remain poorly defined. Herein, we observed significantly lower bone quality and elevated levels of inflammation in bone and bone marrow niche after controlled cortical impact-induced TBI in in-vivo CD-1 mice. Further, we identified dysregulated NFB signaling, an established media… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Traumatic brain injury (TBI) is one of the common causes of disability and death. Patients with TBI often have cognitive dysregulation, dyskinesia, memory impairment and other neurological problems [ 1 ]. TBI has both a direct mechanical effect (primary injury) and an indirect effect caused by a complex pathological cascade (secondary injury).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is one of the common causes of disability and death. Patients with TBI often have cognitive dysregulation, dyskinesia, memory impairment and other neurological problems [ 1 ]. TBI has both a direct mechanical effect (primary injury) and an indirect effect caused by a complex pathological cascade (secondary injury).…”
Section: Introductionmentioning
confidence: 99%
“…41,42 Currently, research on the increased fracture healing and bone callus formation seen in concomitant brain trauma has largely focused on investigating the effect of cytokines and other proteins, while research on the regulation of miRNAs is still lacking. [43][44][45] However, our study found that the expression level of miRNAs-92a-3p was significantly increased in patients with concomitant fractures and brain trauma, as well as in the mouse model. miRNAs-92a-3p can promote the mineralization and maturation of osteoblast precursor cells in vitro, and local injection of agomiR-92a-3p can significantly promote scab formation at the fracture site in mice.…”
Section: Discussionmentioning
confidence: 94%